The Way Poets Read Now - Elizabeth Sarah Coles (Humanities, 2025)
The way literature scholars read now has been under scrutiny for over a decade. The same long decade has seen an explosion in experimental literatures that make reading in the literary-critical sense a matter for poets: a poet’s hybrid, whose disturbance of genre is claimed by publishers as the writing’s main attraction. This paper explores the disturbance of literary criticism in the work of contemporary North American poets, Maureen N. McLane and Lisa Robertson. Asking how these poets read now, the paper argues that an exchange of powers between analysis and performance reorients criticism toward a hybrid ‘dramatic’ mode, activist in its sensibilities and committed to a redistribution of agencies by style and form. Far from deepening the divide between creative and academic criticism, these poets model the significance of composition, prosody, and voice for critical writing of all kinds.